2021
DOI: 10.1021/acs.langmuir.1c00557
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric Cationic Surfactant Coacervation as a Versatile Approach for Removing Organic Pollutants

Abstract: A versatile method to remove a broad spectrum of dye pollutants from wastewater rapidly and efficiently is highly desirable. Here, we report that the complex coacervation of cationic trimeric imine-based surfactants (TISn) with negatively charged hydrolyzed polyacrylamide (HPAM) can be used for this purpose. The coacervation occurs in a wide concentration and composition range and requires the HPAM and TISn concentrations as low as 0.1 g/L and 0.1 mM, respectively. Dye effluents treated by trimeric surfactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Meanwhile, the stronger binding ability of coacervates with water is beneficial for the coacervate to bind with various specific polar microregions at superhydrophobic leaf surfaces and helpful for the surface wettability transition from superhydrophobic to hydrophilic. More specifically, the nanosized network microstructure of coacervates leads to effective encapsulation for a broad range of hydrophilic and hydrophobic solutes as well as the responsive ability to the environment. , These comprehensive features endow the coacervates with more superior properties as pesticide carriers, making sprayed droplets completely deposit and spread and enhancing agrochemical solubilization, stability, and control release. Even more, the entanglement of network-like microstructure with the micro/nanostructures of superhydrophobic surfaces effectively inhibit the wind/rainwater erosion of the droplets after deposition, and the imine groups in the dynamic covalent surfactant endow the coacervate dissociation with CO 2 responsiveness; so, the release of pesticides is controlled by CO 2 in air.…”
Section: Deposition and Spreading Of High-speed Impacted Aqueous Drop...mentioning
confidence: 99%
“…Meanwhile, the stronger binding ability of coacervates with water is beneficial for the coacervate to bind with various specific polar microregions at superhydrophobic leaf surfaces and helpful for the surface wettability transition from superhydrophobic to hydrophilic. More specifically, the nanosized network microstructure of coacervates leads to effective encapsulation for a broad range of hydrophilic and hydrophobic solutes as well as the responsive ability to the environment. , These comprehensive features endow the coacervates with more superior properties as pesticide carriers, making sprayed droplets completely deposit and spread and enhancing agrochemical solubilization, stability, and control release. Even more, the entanglement of network-like microstructure with the micro/nanostructures of superhydrophobic surfaces effectively inhibit the wind/rainwater erosion of the droplets after deposition, and the imine groups in the dynamic covalent surfactant endow the coacervate dissociation with CO 2 responsiveness; so, the release of pesticides is controlled by CO 2 in air.…”
Section: Deposition and Spreading Of High-speed Impacted Aqueous Drop...mentioning
confidence: 99%
“…6), enclosing the curcumin of the entire mixed system. It was reported that hydrophilic dyes could also be well encapsulated in the coacervate compartment and some studies utilized the adsorptive network structure of coacervates as a general method for removing and recovering dyes from wastewater (Liu, Zhao, Shen, Fan, & Wang, 2021;Meng, Schiffman, & Perry, 2018;Shah et al, 2020). Coacervation also played role in biological cells as physicochemical and mechanical filters of pore-like structures, such as nuclear pores (Schmidt & Görlich, 2016).…”
Section: The Effect Of Nacl On the Encapsulation Properties Of Curcum...mentioning
confidence: 99%
“…on the composition and properties of the coacervate and supernatant phases has emerged. 93 The crowded interiors of the coacervates and their ability to sequester charged (bio)macromolecules from their surroundings have promoted their utility as encapsulants and stabilizers in biological, 79,94 industrial, 95–97 environmental, 17,19,83 and cosmetic applications. 81,82…”
Section: Introductionmentioning
confidence: 99%